Sorption of tetracycline on H2O2-modified biochar derived from rape stalk. Issue 1 (1st January 2019) - Tan, Zhenzhen; Zhang, Xueyang; Wang, Liping; Gao, Bin; Luo, Junpeng; Fang, Ru; Zou, Weixin; Meng, Na
ABSTRACT: To determine the sorption potential and mechanisms of tetracycline (TC) on pristine and H2 O2 -modified biochars, rape stalk biochars were produced and modified by H2 O2 . The specific surface area and pore volume of biochars increased with improving pyrolysis temperature, while the acidic groups decreased. Moreover, modified by H2 O2, much more oxygen-containing functional groups were introduced. The results of sorption dynamics and isothermals tests showed that RB300 had the largest TC sorption capacity of 35.90 mg/g, which was ascribed to a plenty of non-carbonized organic matter and surface functional groups were retained. Modified by H2 O2, the sorption of TC on biochars was enhanced which indicated the dominated sorption mechanisms were H-bonding and π–π electron donor acceptor interaction. The pH value would impact on sorption, and the maximum sorption capacity was obtained at pH = 9.0. Both cation concentration and type would affect the TC sorption.